2021
DOI: 10.3390/genes12020299
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Differential Gene and Protein Expression Profiles of Corneal Epithelial Cells Stimulated with Alternating Current Electric Fields

Abstract: In cells, intrinsic endogenous direct current (DC) electric fields (EFs) serve as morphogenetic cues and are necessary for several important cellular responses including activation of multiple signaling pathways, cell migration, tissue regeneration and wound healing. Endogenous DC EFs, generated spontaneously following injury in physiological conditions, directly correlate with wound healing rate, and different cell types respond to these EFs via directional orientation and migration. Application of external D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…As soon as the PNI occurs, endogenous electric fields are generated correspondingly, which may take part in regulating the rate of nerve sprouting, growth, and regeneration. Applied electric fields have likewise been found to influence the regeneration of nerves after injury, i.e., promote survival, migration, and axonal elongation of neurons, either applied immediately following nerve repair or a perioperative ES ( Zarrintaj et al, 2020 ; Kowtharapu et al, 2021 ; Trueman et al, 2022 ). In 1952, Hoffman was the first to apply ES to injured nerve.…”
Section: Application Of Es For Treatment Of Pnimentioning
confidence: 99%
“…As soon as the PNI occurs, endogenous electric fields are generated correspondingly, which may take part in regulating the rate of nerve sprouting, growth, and regeneration. Applied electric fields have likewise been found to influence the regeneration of nerves after injury, i.e., promote survival, migration, and axonal elongation of neurons, either applied immediately following nerve repair or a perioperative ES ( Zarrintaj et al, 2020 ; Kowtharapu et al, 2021 ; Trueman et al, 2022 ). In 1952, Hoffman was the first to apply ES to injured nerve.…”
Section: Application Of Es For Treatment Of Pnimentioning
confidence: 99%
“…32 It is a Shiny application built with many R/Bioconductor programs and a large annotation and pathway database extracted from a variety of sources. 28, 29 It is intended for in-depth gene list analysis, with graphical enrichment visualization and pathway analysis (p-value < 0.05). The hierarchical clustering tree summarizes the relationship between the significant pathways listed in the enrichment tab.…”
Section: Go and Pathway Enrichment Analysismentioning
confidence: 99%
“…6a, b). 29 In clinical application, we found that arsenic resistance genes (arsB, arsC, and arsR) in multidrug-resistant KP and PA can be valuable for researchers in several ways to develop therapeutic use. Salam et al 57 in 2020 studied arsenic resistance genes provided insights into cross-resistance mechanisms between arsenic and antibiotics.…”
Section: Go and Pathway Enrichment Analysismentioning
confidence: 99%
“…The disease alliance analysis showed arteriosclerosis, renal cell carcinoma, Alzheimer's, hypertension, breast cancer, urinary bladder cancer, Parkinson's disease, myocardial infarction, breast carcinoma, etc. The KEGG analysis showed Nitrogen metabolism one of the processes of plant physiology and also one of the important parts of global chemical cycle which can lead to lung adenocarcinoma, prolactin signaling pathway is activated by prolactin-PRLR interaction is the JAK/STAT pathway that can cause tumorigenesis, reproductive abnormalities, and diabetes, Cell cycle is a series of events that takes place in a cell as it grows and divides which may lead to Glaucoma and other retinal disorders, lL-17 signaling pathway initiates signaling through Act1-induced K63-linked ubiquitylation of TRAF6 which can cause diseases such as psoriasis, rheumatoid arthritis (RA), multiple sclerosis, scleroderma, and apoptosis are known to be a form of planned cell death that occurs in multicellular organisms which can lead to Alzheimer's disease, Huntington's disease, and Parkinson's disease [27].…”
Section: Discusssionmentioning
confidence: 99%